World Bank Group Strategy for Fragility, Conflict, and Violence 2020–2025 - World Bank Group (World Bank, Washington, DC, 2020)
By 2030, more than half of the world’s extreme poor will live in countries characterized by fragility, conflict, and violence. Preventing and mitigating fragility, conflict, and violence (FCV) is central to achieving the Sustainable Development Goals (SDGs) and the World Bank Group’s (WBG) twin goals of ending extreme poverty and promoting shared prosperity. The objective of the FCV Strategy is to enhance the WBG’s effectiveness to support countries in addressing the drivers and impacts of FCV and strengthening their resilience, especially for the most vulnerable and marginalized populations.